User elicited gesture-based locomotion techniques for immersive VEs in a seated position: a comparative evaluation - Ganapathi, Priya; Sorathia, Keyur (Frontiers in Virtual Reality, 2023)
Locomotion is a fundamental task for exploring and interacting in virtual environments (VEs), and numerous locomotion techniques have been developed to improve the perceived realism and efficiency of movement in VEs. Gesture-based locomotion techniques have emerged as a more natural and intuitive mode of interaction than controller-based methods of travel in VEs. In this paper, we investigate the intuitiveness, comfort, ease of use, performance, presence, simulation sickness, and user preference of three user-elicited body-based gestures: the Calling gesture, Deictic Pointing gesture, and Mirror Leaning gesture, intended for use in three different multitasking scenarios while seated: Scenario1 (involving virtual travel only), Scenario 2 (involving virtual travel and one hand engaged in selection), and Scenario 3 (involving virtual travel and two hands engaged in selection). The first study involved 30 participants, who compared the Calling gesture with the Tapping and Teleportation gesture for Scenario 1. The second study involved another 30 participants, who compared the Deictic Pointing gesture with the Tapping and Teleportation gesture for Scenario 2. In the third study, a new group of 30 participants compared the Mirror Leaning gesture for Scenario 3 with the Tapping and Teleportation gestures. We compared the gestures of the scenarios in three complementary search tasks: traveling in a straight-line path, moving in a directed path, and moving in an undirected path. Our results indicate that the Calling gesture was the most intuitive gesture for Scenario 1, with increased presence, while the Teleportation gesture was the preferred travel technique. For Scenario 2, we found that the Deictic Pointing gesture was more intuitive than the Tapping and Teleportation gestures in terms of performance, comfort, ease of use, and presence. The Mirror Leaning gesture was the most intuitive gesture for Scenario 3, with increased presence and performance compared to the Tapping and Teleportation gestures. We believe that the qualitative and quantitative measures obtained from our studies will help researchers and interaction design experts to design efficient and effective gesture-based locomotion techniques for traveling in a seated position in multitasking VEs.